Media Matematika Adaptif Berbasis Offline-First Untuk SD Pedesaan: Di SD Negeri 102 Sigalapang - Indah Warni; Almira Amir; Khairunnisa; Tuti Alawiyah Matondang (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2026)
This study developed and evaluated the impact of an offline-first adaptive mathematics learning platform on the conceptual understanding and digital self-efficacy of rural primary school students. Utilizing a sequential explanatory mixed-methods design integrated with Design-Based Research, the study involved 87 students from SD Negeri 102 Sigalapang over a six-week intervention. Quantitative analysis via ANCOVA revealed significant improvements in conceptual understanding (Δ = +13.3 points; p < .001; ηp² = 0.183) and digital self-efficacy (Δ = +1.06; p < .001; ηp² = 0.145). Qualitative findings identified the psychopedagogical mechanisms underlying these outcomes: interface predictability reduced extraneous cognitive load, adaptive branching facilitated autonomy without stigma, and immediate feedback reinforced mastery experiences. The frequency of task abandonment decreased from 34.2% to 9.1%, confirming sustained engagement within resource-constrained environments. The study concludes that offline-first adaptive mathematics learning represents a cognitively and affectively sound pedagogical strategy, rather than merely a technical workaround. These findings offer a replicable framework for developing inclusive educational technologies in emerging markets, while underscoring that digital equity in mathematics education necessitates designs responsive to local infrastructural realities.